ITIL Service design - Hunnebeck, Lou (TSO (The Stationery Office) NorwichGB, 2011)
Provides guidance on how to view service managment not only as an organisational capability but as a strategic asset. Describes the principles underpinning the practice of service management which are useful for developing service management policies, guidelines and processes across the ITIL service lifecycle.